Ontology Usability Scale: Context-aware Metrics for the Effectiveness, Efficiency and Satisfaction of Ontology Uses. (10th May 2018) - Ma, Xiaogang; Fu, Linyun; West, Patrick; Fox, Peter
Both ontology builders and users need a way to evaluate ontologies in terms of usability, but existing ontology evaluation approaches do not fit this purpose. We propose the Ontology Usability Scale (OUS), a ten-item Likert scale derived from statements prepared according to a semiotic framework and an online poll in the Semantic Web community to provide a practical way of ontology usability evaluation. Case studies were conducted to bookkeep current usability evaluation results for ontologies expecting revisions in the future, and discussions of the poll results are presented to help proper use and customization of the OUS.